Enterobacteriaceae Sepsis Outcome Programme annual report, 2013 - Turnidge, J.; Gottlieb, T.; Mitchell, D.; Coombs, Geoffrey; Daley, D.; Bell, J. (2014)
The Australian Group on Antimicrobial Resistance performs regular period-prevalence studies to monitor changes in antimicrobial resistance in selected enteric Gram-negative pathogens. The 2013 survey focussed for the first time on blood stream infections. Four thousand nine hundred and fifty-eight Enterobacteriaceae species were tested using commercial automated methods (Vitek® 2, BioMérieux; Phoenix™, BD). The results were analysed using Clinical and Laboratory Standards Institute (CLSI) and European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints (January 2014). Of the key resistances, non-susceptibility to the third-generation cephalosporin, ceftriaxone, was found in 7.5%/7.5% (CLSI/EUCAST criteria respectively) of Escherichia coli; 6.3%/6.3% of Klebsiella pneumoniae, and 7.4%/7.4% of K. oxytoca. Non-susceptibility rates to ciprofloxacin were 10.3%/11.3% for E. coli, 4.6%/7.5% for K. pneumoniae, 0.6%/0.6% for K. oxytoca, and 3.6%/6.1% in Enterobacter cloacae. Resistance rates to piperacillin-tazobactam were 3.1%/6.2%, 4.2%/7.0%, 11.9% /12.6%, and 17.3% /22.2% for the same 4 species respectively. Fourteen isolates were shown to harbour a carbapenemase gene, 9 blaIMP, 3 blaKPC, and 2 blaNDM.